Engineering properties of Phra Wihan sandstone in Thailand - Chang, Shun-chung; Prinya Nutalaya; Brenner, R.P.; Ohta, Hideki; R.S.E.A. (R.O.C.) (Bangkok : Asian Institute of Technology, 1981)
Phra Wihan Sandstone from 7 locations were collected from the Khorat Plateau in Thailand. Its physical, mechanical and mineralogical properties were studied in detail in the laboratory. The correlations between various properties were established. The results show that the porosity and schmidt rebound number are the suitable index properties for making rapid assessments of rock strength in the Phra Wihan Sandstone. The average porosity and Schmidt rebound number of this sandstone are 7.80% and 48 .5, the corresponding unconfined compressive strength and Brazilian tensile strength are 85.58 MPa and 7.92 MPa respectively.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1981
Keywords: Sandstone -- Thailand -- Khorat -- Testing